Інформаційне забезпечення безпеки навчально-виховного процесу загальноосвітніх навчальних закладів України - Євтушенко, Ольга Володимирівна (My University, 2014)
Представлена стаття присвячена розробці інформаційної системи для моніторингу та контролю навчального процесу загальноосвітніх навчальних закладів України. Запропоновано використання даного інформаційного ресурсу під час проведення профорієнтаційної роботи викладачами НУХТ серед випускників загальноосвітніх навчальних закладів України. This article is dedicated to a data development system for control and safety monitoring of the educational process in general educational institutions of Ukraine. The offered informational system represents a quite useful informational resource not only for all elements of secondary education, but also for parent’s as a quick way to be informed about child’s studying process. With the help of this system, parents have the ability to obtain information including marks, attendance, and school notifications (for example teacher-parent meeting). The system allows parents to be always aware of theirs children success level and to stay in touch with teachers and school administration.
Keywords: загальноосвітній заклад; інформаційна система; інформаційний ресурс; користувач; general educational institution; informational system; informational resource; user; кафедра екології та екоменеджменту